AN AGRICULTURAL DEVELOPMENT LEGACY UNREALISED BY FIVE PRESIDENTS, 1966–2014 - Tjondronegoro, Sediono M.P. (Masyarakat Indonesia, 2013)
The founding fathers of the Indonesian Republic, Soekarno and Moh. Hatta, who became first President and Vice President respectively, designated the agricultural sector as the major factor contributing to Indonesia’s economic growth. Prof Anne Booth’s research findings during the Green Revolution in the mid-1970s also indicate the importance of the agricultural sector. Food self-sufficiency in the country was achieved in 1985, when Indonesia was close to its “take-off” stage. However, subsequent developments after the New Order period indicated a gradual shift of policy guide lines from People’s Welfare to Export-driven Growth and Increasing Foreign investment. Five Presidents since Sukarno have neglected the urgency of agrarian reform in Indonesia.